PENGUKURAN KINERJA RUMAH SAKIT DENGAN PENDEKATAN BALANCED SCORECARD (Studi Kasus Pada RSUD dr. Doris Sylvanus Palangka Raya) - Pamungkur, Pamungkur .; Sunarmie, Sunarmie (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2025)
The aim of this research is to measure performance of RSUD Dr. Doris Sylvanus Palangka Raya through Balanced Scorecard. The measurement is divided into four perspectives : financial, learning and growth, internal business process, and customer perspective. This primary and secondary data of this research are derived from 2021 up to 2023. The results of the study show that RSUD Dr. Doris Sylvanus Palangka Raya in general has performed well. The financial perspective analysis shows a good results as indicated by the increase of efficiency and ROI. However, in terms of the learning and growth, internal business process, and customer perspective, the Hospital is considered as performing adequately and thus needs some improvements in some aspects, especially employee turnover, BOR, ALOS, TOI, complain level, and customer retention.